Membaca Adalah Jendela Dunia: Optimalisasi Sudut Baca dan Papan Literasi Pada Peserta Didik di SD Negeri 2 Tomohon - Monigir, Norma (Peneliti.net, 2025)
Literacy culture plays a strategic role in shaping the character and thinking skills of students from an early age. However, low reading interest among elementary school students remains a challenge in various regions, including at Tomohon 2 Public Elementary School. This community service activity aims to optimize reading corners and literacy boards to increase students' interest and literacy skills. The methods used included initial observation, designing and providing reading corners, creating interactive literacy boards, teacher training, and participatory evaluation. The results of the activity showed an increase in student enthusiasm for reading and expressing their reading experiences through the literacy boards. The reading corners provide a conducive alternative space for learning, while the literacy boards serve as a medium for student communication and expression. The conclusion of this activity is that providing attractive and functional literacy facilities can significantly encourage the growth of a reading culture in elementary schools.